(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Data about qualitative and quantity composition of phenolic acids and flavons together with the content of flavonols and leucoanthocyanins in water-ethanolic extracts from two species of Achillea L. is given in the article. Predominant components is determined. It is revealed that the content of flavonols and leucoanthocyanins in extracts depends of the species of Achillea L.